Vietnam signing Regional Seed Cooperation (Seed without border) to collaborate in seed sector. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
After organizing a policy forum and circulating a position paper, Vietnamese Ministry of Agriculture and Rural Development (MARD) has decided to join the Regional Seed Cooperation.